2015
DOI: 10.1111/dth.12222
|View full text |Cite
|
Sign up to set email alerts
|

Off-label use of TNF-alpha inhibitors in a dermatological university department: retrospective evaluation of 118 patients

Abstract: Tumor necrosis factor-alpha (TNF)-alpha inhibitors are licensed for patients with severe refractory psoriasis and psoriatic arthritis. However, TNF-alpha inhibitors have also been used off-label for various recalcitrant mucocutaneous diseases. This study aimed to evaluate the efficacy and safety of TNF-alpha inhibitors used for off-label dermatological indications. We retrospectively evaluated patient records of 118 patients treated off-label with TNF-alpha inhibitors in a dermatological university department.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 28 publications
2
59
0
5
Order By: Relevance
“…Of all patients, 39·6% were previously treated with prednisolone and 26·0% had been treated with dapsone or one or more immunosuppressant drugs such as ciclosporin A, azathioprine, mycophenolate mofetil, methotrexate and/or tumour necrosis factor (TNF) inhibitors. We have previously reported that among a subset of 25 patients with chronic urticaria who were naïve to biological drugs or who had received omalizumab, 60% obtained complete or almost complete resolution of urticaria and angioedema after onset of therapy with either adalimumab or etanercept, whereas another 15% of patients experienced a partial response to treatment with these TNF inhibitors …”
Section: Characteristics Of 154 Patients With Chronic Spontaneous Urtmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all patients, 39·6% were previously treated with prednisolone and 26·0% had been treated with dapsone or one or more immunosuppressant drugs such as ciclosporin A, azathioprine, mycophenolate mofetil, methotrexate and/or tumour necrosis factor (TNF) inhibitors. We have previously reported that among a subset of 25 patients with chronic urticaria who were naïve to biological drugs or who had received omalizumab, 60% obtained complete or almost complete resolution of urticaria and angioedema after onset of therapy with either adalimumab or etanercept, whereas another 15% of patients experienced a partial response to treatment with these TNF inhibitors …”
Section: Characteristics Of 154 Patients With Chronic Spontaneous Urtmentioning
confidence: 99%
“…We have previously reported that among a subset of 25 patients with chronic urticaria who were na€ ıve to biological drugs or who had received omalizumab, 60% obtained complete or almost complete resolution of urticaria and angioedema after onset of therapy with either adalimumab or etanercept, whereas another 15% of patients experienced a partial response to treatment with these TNF inhibitors. 2,3 The initial dose of omalizumab given was 150 mg every 2 weeks in 45Á5% of cases and 300 mg every 4 weeks in 55% of cases (Table 1). At the time of treatment, use of omalizumab for CSU was still off-label.…”
mentioning
confidence: 99%
“…exazerbieren diese, bezeichnet man sie als "paradox": Plaque-Psoriasis, Psoriasis palmoplantaris pustulosa, Psoriasis pustulosa generalisata (Zumbusch), Akne inversa, Lupus erythematodes (kutane Form, drug-induced), Vaskulitiden, bullöse Dermatosen, Granuloma anulare, Lichen ruber planus, Alopecia areata, Vitiligo und Sarkoidose [ 8 ] . Treten die folgenden Dermatosen unter TNF α -Inhibition neu auf, bzw.…”
Section: Immunvermittelte Reaktionen Sowie Andere Komplikationenunclassified
“…In Deutschland sind derzeit vier TNF α -Antikörper (Infl iximab, Adalimumab, Certolizumab, Golimumab) sowie das Rezeptorfusionsmolekül Etanercept zugelassen (Tabelle 1 ). Neben den Indikationen rheumatoide Arthritis, ankylosierende Spondylitis, Psoriasis, Psoriasis-Arthritis, Morbus Crohn, Colitis ulcerosa, Hidradenitis suppurativa und Uveitis gibt es Berichte über erfolgreiche experimentelle Anwendung im Off-Label-Use unter anderem bei Psoriasis pustulosa, subkornealer Pustulose, Pityriasis rubra pilaris, Morbus Behçet, Granuloma anulare, Granuloma anulare disseminatum, Pyoderma gangraenosum, und bullösen Autoimmundermatosen [ 7,8 ] .…”
unclassified
“…• TNF-α inhibitors (e.g. Infliximab) have successfully been used off-label in adults for the treatment of granulomatous rosacea [29]. Cytokines, chemokines, and Toll-like receptors may become potential targets for future therapeutic interventions in rosacea and possibly BKC.…”
Section: Pathophysiologymentioning
confidence: 99%